DBT skills training handouts and worksheets - Linehan, Marsha, 1943- (The Guilford Press, 2015)
Featuring more than 225 user-friendly handouts and worksheets, this is an essential resource for clients learning dialectical behavior therapy (DBT) skills, and those who treat them. All of the handouts and worksheets discussed in Marsha M. Linehan's DBT Skills Training Manual, Second Edition, are provided, together with brief introductions to each module written expressly for clients. Originally developed to treat borderline personality disorder, DBT has been demonstrated effective in treatment of a wide range of psychological and emotional problems. No single skills training program will include all of the handouts and worksheets in this book; clients get quick, easy access to the tools recommended to meet their particular needs. The 8 1/2" x 11" format and spiral binding facilitate photocopying. Purchasers also get access to a webpage where they can download and print additional copies of the handouts and worksheets.